Crystal Structure and Thermodecomposition Kinetics of Copper(II) Ternary Complex with o-Vanillin-taurine Schiff-base and 1,10-Phenanthroline† - YANG, LI-RONG; BI, CAI-FENG; FAN, YU-HUA; LU, SI-QUAN; GUO, FENG; AI, XIAO-KANG (Asian Journal of Chemistry, 2010)
A complex of copper(II) with o-vanillin-taurine Schiff base and 1,10-phenanthroline (1,10-phen) (C22H25CuN3O8S, Mr= 555.05), has been synthesized and characterized by IR, elemental analysis and X -ray diffraction single crystal analysis. The crystal belongs to monoclinic, space group P2(1)/c with a = 14.8310(16) Å, α = 90.00°, b = 26.580(3) Å, β = 112.890(2)°, σ = 12.8486(14) Å, γ = 90.00°, V = 4666.2(9) Å3, Z = 8, F(000) = 2296, Dc = 1.580 g/cm3, μ = 1.080 mm-1. In the molecule, the Schiff base and 1,10-phen act as tridentate and bidentate ligands, respectively, to form a distorted triangle bipyramid geometry. The prominent feature of the complex is that taurine in the Schiff base offers S03 as a donor. The thermal decomposition kinetics of the complex have been investigated under non-isothermal condition using the Achar differential method and the Coats-Redfern integral method. The kinetic equation (of step (3)) may be expressed as follows: da/dt = A . e(-E/RT) . 3/2[(1 - a)-1/3 - 1, E = 72.42 kJ/mol, In A = 14.70.